Valorization of green biomass Azolla pinnata fern: multi‐parameter evaluation of processing conditions on protein extractability and their influence on the physicochemical, structural, techno‐functional properties and protein quality. (27th June 2022) - Qoms, Mohammed S; Arulrajah, Brisha; Shamsudin, Rosnah; Ibadullah, Wan Zunairah Wan; Saari, Nazamid
Abstract: BACKGROUND: This study determined the effect of processing conditions on protein extractability from Azolla pinnata fern, and their influence on the physicochemical, structural, techno‐functional properties and protein quality. RESULTS: The protein extraction from A. pinnata fern was optimized through response surface methodology obtaining a maximum yield of 18.93% with a recovery rate of 73.66%. The A. pinnata fern protein concentrate (AFPC) had five protein bands with a molecular weight ranging from 17 to 56 kDa. AFPC contained high β‐sheet structure (36.61%), favouring its good thermal properties with three endothermic peaks at 54.28, 86.52 and 166.25 °C. The AFPC scored ≥ 1 for all essential amino acids, except for lysine and histidine. The AFPC exhibited exceptionally high techno‐functional properties, particularly for water holding (5.46 g g −1 ) and fat absorption capacity (10.08 g g −1 ), and gelling properties (5% gelation concentration). The AFPC had high in vitro digestibility of 73%, signifying its high availability for human consumption. CONCLUSION: The underexploited A. pinnata fern is a potential source of edible protein, thus a promising nutraceutical or ingredient of functional and health‐promoting foods. © 2022 Society of Chemical Industry.